PERAN DOSEN MEMANFAATKAN TEKNOLOGI PENDIDIKAN DALAM MENINGKATKAN MOTIVASI DAN KUALITAS PEMBELAJARAN DI STAIN PADANGSIDIMPUAN - Daulae, Tatta Herawati (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThe problem of this research is any type of educational technology lecturer at STAIN Padangsidimpuan utilized, how the role of faculty utilize educational technology in improving the quality of learning and motivation in Padangsidimpuan STAIN. The purpose of the study to determine the types of educational technology that is used to determine the role of faculty and faculty use. The research methodology was qualitative descriptive in describing a systematic, data collection tools interviews and observation. The analysis consists of domain analysis taxonomy, kompensial and cultural theme. The results of this study indicate that the role of faculty utilize educational technology in improving the quality of learning and motivation in STAIN Padangsidimpuan high enough, this can be proved by the standard of competence held by students after participating in learning activities more effectively, as well as meticulous and thorough mastery of the course and the learning outcomes increased .Kata Kunci : Dosen, Teknologi, Motivasi, Pembelajaran.